Oganizational resource management theories, methodologies, & applications - Kantola, Jussi (CRC Press, Taylor & Francis Group, 2016)
The management of organizational resources is extremely difficult. Managers face serious and complex challenges when managing the required resources for the benefit of their organization. This book presents a unique approach that aims to tackle these management challenges. This approach is based on four propositions that together form a solid framework for the management of organizational resources. The propositions state that organizational resources that are considered as management objects must first be conceptually modeled. With the help of these models, stakeholders are integrated into the management process